Composite additive for nonaqueous electrolyte, nonaqueous electrolyte, and lithium ion battery
Patent Information
- Application Number
- CN202611108291.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-24
- Publication Date
- 2026-10-23
AI Technical Summary
然而,现有技术中,常规含硫添加剂(如硫酸酯类、磺内酯类化合物)在负极表面形成的SEI膜以无机盐组分为主,膜层脆性大、柔韧性不足,在高温或电极体积变化条件下难以保持结构完整性和界面覆盖的致密性;含硅添加剂虽具有一定的除酸功能,但其单独使用时成膜能力有限、界面阻抗较高
本发明通过含硫的第一添加剂与含硅的第二添加剂的协同配合,在电极表面原位构建有机-无机复合界面膜。含硫添加剂中的不饱和烃基发生自由基聚合,形成柔韧、致密且耐高温的聚烯烃类聚合物膜,并与还原产生的无机锂盐组分协同,赋予界面膜优异的结构稳定性和离子传导性;含硅添加剂则同步发挥除酸、除水及稳定锂盐的功能,有效抑制了含硫添加剂可能引起的电解液酸度升高和正极腐蚀问题,二者功能互补,实现了界面保护层的多重优化。
Smart Images

Figure SMS_46 
Figure QLYQS_1 
Figure QLYQS_2
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium battery technology, specifically to a composite additive for non-aqueous electrolytes, a non-aqueous electrolyte, and a lithium-ion battery. Background Technology
[0002] Lithium-ion batteries have been widely used in power batteries and energy storage batteries due to their high energy density and long cycle life. However, in high-temperature environments, the electrolyte is prone to chemical or electrochemical reactions, leading to instability of the SEI film on the negative electrode surface, accelerated battery capacity decay, and increased internal resistance, which severely restricts their reliability in high-temperature applications.
[0003] Forming a stable, low-impedance interfacial protective film on the electrode surface through electrolyte additives is an effective way to improve the high-temperature performance of lithium-ion batteries. Both sulfur-containing and silicon-containing compounds have been explored as functional electrolyte additives. However, in existing technologies, conventional sulfur-containing additives (such as sulfate esters and sulfonyl lactones) form an SEI film on the negative electrode surface that is mainly composed of inorganic salts. This film is brittle and lacks flexibility, making it difficult to maintain structural integrity and interfacial density under high temperatures or electrode volume changes. While silicon-containing additives have some acid removal capabilities, their film-forming ability is limited and their interfacial impedance is high when used alone. Currently, there is a lack of electrolyte additive solutions that can balance excellent high-temperature performance with low interfacial impedance. Summary of the Invention
[0004] In view of this, the present invention provides a composite additive for non-aqueous electrolytes, a non-aqueous electrolyte, and a lithium-ion battery. Through the synergistic effect of sulfur-containing additives and silicon-containing additives containing unsaturated hydrocarbon groups, a dense, flexible, and high-temperature resistant organic-inorganic composite interface film is formed on the electrode surface. At the same time, the increase in electrolyte acidity is suppressed, which significantly improves the high-temperature storage performance and high-temperature cycle performance of lithium-ion batteries, while maintaining a low interface impedance.
[0005] To achieve the above objectives, the technical solution adopted by the present invention is as follows: In a first aspect, the present invention discloses a composite additive for non-aqueous electrolytes, comprising a first additive and a second additive; the first additive accounts for 0.9% to 3.0% of the total mass of the non-aqueous electrolyte; the second additive accounts for 0.1% to 1.5% of the total mass of the non-aqueous electrolyte; wherein: The general structural formula of the first additive is: ; In the formula, at least one of R1 and R2 is selected from F or fluorinated C. 6~12 Aryl, fluorinated C 6~12 heteroaryl or fluorinated C 1~3 Alkyl; and at least one of R1 and R2 is selected from substituted or unsubstituted C. 1~3Unsaturated alkyl groups.
[0006] The general structural formula of the second additive is ; In the formula, R1, R2, R3, and R4 are each independently selected from C1-C5 saturated hydrocarbon groups, unsaturated hydrocarbon groups, halohydrocarbon groups, cyclic hydrocarbon groups, cyano groups, and phenyl groups, and at least one of R1, R2, R3, and R4 is selected from substituted or unsubstituted C1-C5 groups. 1~3 Unsaturated alkyl groups.
[0007] As a further aspect of the present invention: the first additive is CH2=CH SO2 F (vinyl sulfonyl fluoride), CF2=C(F) SO2 F (1,2,2-trifluorovinylsulfonyl fluoride), CH2=C(CF3) SO2 F (2-(trifluoromethyl)ethylenesulfonyl fluoride), CH2=CH SO2 At least one of CF3 (vinyltrifluoromethyl sulfone).
[0008] As a further aspect of the present invention: the second additive is CH2=CH Si(CH3)3 (trimethylvinylsilane), CH2=CH Si(CH3)2 CH=CH2 (dimethyldivinylsilane), F CH=CH At least one of Si(CH3)3 (trimethyl-2-fluorovinylsilane).
[0009] Secondly, the present invention discloses a non-aqueous electrolyte comprising the composite additives, lithium salt, lithium fluorosulfonate and organic solvent as described above, wherein the lithium fluorosulfonate has a mass percentage content of 0.05% to 0.5% in the non-aqueous electrolyte.
[0010] As a further aspect of the present invention, the lithium salt is selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium dioxalate borate, lithium difluorooxalate borate, lithium difluorooxalate phosphate, lithium bis(fluorosulfonyl)imide, and lithium bis(trifluoromethylsulfonyl)imide.
[0011] As a further aspect of the present invention, the organic solvent is selected from at least one of cyclic carbonates, chain carbonates, cyclic carboxylic esters, chain carboxylic esters, cyclic ethers, chain ethers, tetrahydrofuran, 2-methyltetrahydrofuran, and 1,3-dioxolane.
[0012] As a further aspect of the present invention, it also includes conventional additives, wherein the conventional additives are selected from one or more of vinylene carbonate, fluoroethylene carbonate, vinyl sulfate, 1,3-propane sulpholactone, 1,4-butane sulpholactone, methanedisulfonate, tris(trimethylsilane) phosphate, and tris(trimethylsilane) borate; the conventional additives are present in the non-aqueous electrolyte at a mass percentage of 0.1% to 5%.
[0013] Thirdly, the present invention discloses a battery comprising a positive electrode, a negative electrode, a separator located between the positive electrode and the negative electrode, and a non-aqueous electrolyte as described above.
[0014] As a further aspect of the present invention: the positive electrode sheet includes a positive current collector and a positive active material layer disposed on the positive current collector, the positive active material layer containing a positive active material, the positive active material being lithium phosphate with an olivine structure and / or lithium nickel cobalt manganese oxide or lithium nickel cobalt aluminum oxide with a layered structure.
[0015] As a further aspect of the present invention: the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on the negative electrode current collector, the negative electrode active material layer containing a negative electrode active material, the negative electrode active material being one or more of natural graphite, artificial graphite, silicon, and lithium titanate.
[0016] Compared with the prior art, the beneficial effects of the present invention are: This invention utilizes the synergistic effect of a sulfur-containing first additive and a silicon-containing second additive to construct an organic-inorganic composite interface film in situ on the electrode surface. The unsaturated hydrocarbon groups in the sulfur-containing additive undergo free radical polymerization to form a flexible, dense, and high-temperature-resistant polyolefin polymer film, which, in conjunction with the inorganic lithium salt component generated during reduction, imparts excellent structural stability and ionic conductivity to the interface film. The silicon-containing additive simultaneously performs functions of deacidification, dehydration, and lithium salt stabilization, effectively suppressing the potential increase in electrolyte acidity and cathode corrosion caused by the sulfur-containing additive. The complementary functions of the two additives achieve multiple optimizations of the interface protective layer.
[0017] Based on the aforementioned synergistic mechanism, the non-aqueous electrolyte of this invention significantly suppresses side reactions at the electrode interface, substantially reduces the dissolution of transition metal ions, effectively controls gas generation at high temperatures, and maintains a low interfacial impedance. Furthermore, the electrolyte's chemical stability is enhanced by the deacidification and dehydration processes, effectively extending its service life and providing a long-term stable working environment for the electrochemical system.
[0018] The lithium-ion battery using the non-aqueous electrolyte of this invention combines excellent high-temperature storage stability, high-temperature cycle life, and good power characteristics. Its high-temperature performance is significantly superior to existing technologies, without sacrificing rate discharge and charge / discharge power capabilities. This comprehensive performance advantage makes this invention particularly suitable for applications such as power batteries and energy storage batteries with stringent requirements for high-temperature reliability, long lifespan, and safety, and it has broad prospects for industrialization. Detailed Implementation
[0019] To facilitate understanding of the present invention, a more comprehensive description will be given below with reference to specific embodiments. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. Rather, these embodiments are provided to provide a more thorough and complete understanding of the disclosure of the present invention.
[0020] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the description of the invention is for the purpose of describing particular embodiments only and is not intended to be limiting of the invention.
[0021] In addition, unless otherwise specified, the preparation processes in the following embodiments are all conventional methods in the prior art, and therefore will not be described in detail; unless otherwise specified, the parts in the following embodiments refer to parts by weight.
[0022] Example 1 1. Preparation of non-aqueous electrolytes Ethylene carbonate (EC) and ethyl methyl carbonate (EMC) were mixed thoroughly at a mass ratio of EC:EMC = 3:7 to obtain an organic solvent. Lithium hexafluorophosphate (LiPF6) was added to the mixed organic solvent and stirred until the lithium salt was completely dissolved to obtain a lithium salt solution. Subsequently, conventional additives vinylene carbonate (VC), lithium fluorosulfonate (LiFS), a first additive, and a second additive were added to the lithium salt solution and stirred thoroughly to obtain a non-aqueous electrolyte.
[0023] In the non-aqueous electrolyte, the concentration of lithium hexafluorophosphate is 1M, the mass percentage of vinylene carbonate is 1.5%, the mass percentage of lithium fluorosulfonate is 0.3%, the mass percentage of the first additive is 1.5%, and the mass percentage of the second additive is 1.0%. The remainder is an organic solvent.
[0024] The structural formula of the first additive is as follows: The structural formula of the second additive is .
[0025] 2. Preparation of the positive electrode sheet The ternary cathode active material LiNi00.7 C0 0.1 Mn 0.2 Conductive agent Super P, binder polyvinylidene fluoride (PVDF), and carbon nanotubes (CNTs) were mixed evenly at a mass ratio of 97.2:1.8:1:1 to prepare a positive electrode slurry. The positive electrode slurry was uniformly coated on both sides of an aluminum foil, dried at 85°C, cold-pressed, slit and sliced, and then dried under vacuum at 85°C for 4 hours to obtain the positive electrode sheet.
[0026] 3. Preparation of negative electrode sheet Artificial graphite, conductive agent Super P, thickener carboxymethyl cellulose (CMC), and binder styrene-butadiene rubber latex (SBR) were mixed evenly at a mass ratio of 94.5:1.5:1.5:2.5 to prepare a negative electrode slurry. The negative electrode slurry was uniformly coated on both sides of a copper foil, dried, rolled, and then dried under vacuum at 85°C for 4 hours to obtain the negative electrode sheet.
[0027] 4. Assembly of lithium-ion batteries The prepared positive electrode, negative electrode, and separator were stacked to form a battery cell, which was then vacuum-baked at 85°C for 48 hours. The battery cell was placed in a battery casing, and the prepared non-aqueous electrolyte was injected. After encapsulation, formation, and aging processes, a lithium-ion battery with a capacity of 3Ah was obtained.
[0028] Example 2 1. Preparation of non-aqueous electrolytes Ethylene carbonate (EC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC) were mixed in a mass ratio of EC:DMC:EMC = 3:2:5 to obtain an organic solvent. Lithium hexafluorophosphate (LiPF6) and lithium bisfluorosulfonyl imide (LiFSI) were then added. After the lithium salts were completely dissolved, ethylene carbonate (VC), lithium fluorosulfonate (LiFS), the first additive, and the second additive were added to obtain a non-aqueous electrolyte.
[0029] In the non-aqueous electrolyte, the concentration of lithium hexafluorophosphate is 0.9M, the concentration of lithium difluorosulfonyl imide is 0.1M, the mass percentage of vinylene carbonate is 1.5%, the mass percentage of lithium fluorosulfonate is 0.5%, the mass percentage of the first additive is 1.2%, the mass percentage of the second additive is 1.3%, and the remainder is an organic solvent.
[0030] The structural formula of the first additive is: The structural formula of the second additive is: .
[0031] Steps 2-4 are performed in accordance with Example 1.
[0032] Example 3 1. Preparation of non-aqueous electrolytes: Ethylene carbonate (EC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC) were mixed in a mass ratio of EC:DMC:EMC = 3:2:5 to obtain an organic solvent. Lithium hexafluorophosphate (LiPF6) and lithium bisfluorosulfonyl imide (LiFSI) were then added. After the lithium salts were completely dissolved, ethylene carbonate (VC), lithium fluorosulfonate (LiFS), the first additive, and the second additive were added to obtain a non-aqueous electrolyte.
[0033] In the non-aqueous electrolyte, the concentration of lithium hexafluorophosphate is 0.8M, the concentration of lithium difluorosulfonyl imide is 0.2M, the mass percentage of vinylene carbonate is 1.5%, the mass percentage of lithium fluorosulfonate is 0.5%, the mass percentage of the first additive is 1.0%, the mass percentage of the second additive is 1.5%, and the remainder is an organic solvent.
[0034] The structural formula of the first additive is as follows: The structural formula of the second additive is .
[0035] Steps 2-4 are performed in accordance with Example 1.
[0036] Example 4 Ethylene carbonate (EC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC) were mixed in a mass ratio of EC:DMC:EMC = 3:2:5 to obtain an organic solvent. Lithium hexafluorophosphate (LiPF6) and lithium bisfluorosulfonyl imide (LiFSI) were then added. After the lithium salts were completely dissolved, ethylene carbonate (VC), lithium fluorosulfonate (LiFS), the first additive, and the second additive were added to obtain a non-aqueous electrolyte.
[0037] In the non-aqueous electrolyte, the concentration of lithium hexafluorophosphate is 0.7M, the concentration of lithium difluorosulfonyl imide is 0.3M, the mass percentage of vinylene carbonate is 1.5%, the mass percentage of lithium fluorosulfonate is 0.5%, the mass percentage of the first additive is 1.8%, the mass percentage of the second additive is 0.7%, and the remainder is an organic solvent.
[0038] The structural formula of the first additive is as follows: The structural formula of the second additive is .
[0039] Steps 2-4 are performed in accordance with Example 1.
[0040] Example 5 1. Preparation of non-aqueous electrolytes: Ethylene carbonate (EC) and ethyl methyl carbonate (EMC) were mixed at a mass ratio of EC:EMC = 3:7 to obtain an organic solvent; lithium hexafluorophosphate (LiPF6) was then added, and after the lithium salt was completely dissolved, vinylene carbonate (VC), lithium fluorosulfonate (LiFS), the first additive, and the second additive were added to obtain a non-aqueous electrolyte.
[0041] In the non-aqueous electrolyte, the concentration of lithium hexafluorophosphate is 1M, the mass percentage of vinylene carbonate is 1.5%, the mass percentage of lithium fluorosulfonate is 0.5%, the mass percentage of the first additive is 2.0%, the mass percentage of the second additive is 0.5%, and the remainder is an organic solvent.
[0042] The structural formula of the first additive is as follows: The structural formula of the second additive is .
[0043] Steps 2-4 are performed in accordance with Example 1.
[0044] Example 6 1. Preparation of non-aqueous electrolytes: Ethylene carbonate (EC), diethyl carbonate (DEC), and methyl ethyl carbonate (EMC) were mixed in a mass ratio of EC:DEC:EMC = 3:2:5 to obtain an organic solvent. Lithium hexafluorophosphate (LiPF6) and lithium bisfluorosulfonyl imide (LiFSI) were then added. After the lithium salts were completely dissolved, ethylene carbonate (VC), lithium fluorosulfonate (LiFS), the first additive, and the second additive were added to obtain a non-aqueous electrolyte.
[0045] In the non-aqueous electrolyte, the concentration of lithium hexafluorophosphate is 0.9M, the concentration of lithium difluorosulfonyl imide is 0.1M, the mass percentage of vinylene carbonate is 1.5%, the mass percentage of lithium fluorosulfonate is 0.5%, the mass percentage of the first additive is 1.6%, the mass percentage of the second additive is 0.9%, and the remainder is an organic solvent.
[0046] The structural formula of the first additive is as follows: The structural formula of the second additive is .
[0047] Steps 2-4 are performed in accordance with Example 1.
[0048] Example 7 1. Preparation of non-aqueous electrolytes: Ethyl carbonate (EC), ethyl acetate (EA), and methyl methyl carbonate (EMC) were mixed in a mass ratio of EC:EA:EMC = 3:2:5 to obtain an organic solvent. Lithium hexafluorophosphate (LiPF6) and lithium bisfluorosulfonyl imide (LiFSI) were then added. After the lithium salts were completely dissolved, ethylene carbonate (VC), lithium fluorosulfonate (LiFS), the first additive, and the second additive were added to obtain a non-aqueous electrolyte.
[0049] In the non-aqueous electrolyte, the concentration of lithium hexafluorophosphate is 0.8M, the concentration of lithium difluorosulfonyl imide is 0.2M, the mass percentage of vinylene carbonate is 1.5%, the mass percentage of lithium fluorosulfonate is 0.2%, the mass percentage of the first additive is 1.7%, the mass percentage of the second additive is 0.8%, and the remainder is an organic solvent.
[0050] The structural formula of the first additive is as follows: The structural formula of the second additive is .
[0051] Steps 2-4 are performed in accordance with Example 1.
[0052] Example 8 1. Preparation of non-aqueous electrolytes: Ethylene carbonate (EC), diethyl carbonate (DEC), and methyl ethyl carbonate (EMC) were mixed in a mass ratio of EC:DEC:EMC = 3:2:5 to obtain an organic solvent. Lithium hexafluorophosphate (LiPF6) and lithium bisfluorosulfonyl imide (LiFSI) were then added. After the lithium salts were completely dissolved, ethylene carbonate (VC), lithium fluorosulfonate (LiFS), the first additive, and the second additive were added to obtain a non-aqueous electrolyte.
[0053] In the non-aqueous electrolyte, the concentration of lithium hexafluorophosphate is 0.7M, the concentration of lithium difluorosulfonyl imide is 0.3M, the mass percentage of vinylene carbonate is 1.5%, the mass percentage of lithium fluorosulfonate is 0.2%, the mass percentage of the first additive is 1.9%, the mass percentage of the second additive is 0.6%, and the remainder is an organic solvent.
[0054] The structural formula of the first additive is as follows: The structural formula of the second additive is .
[0055] Steps 2-4 are performed in accordance with Example 1.
[0056] Example 9 1. Preparation of non-aqueous electrolytes: Ethylene carbonate (EC) and ethyl methyl carbonate (EMC) were mixed at a mass ratio of EC:EMC = 3:7 to obtain an organic solvent; lithium hexafluorophosphate (LiPF6) was then added, and after the lithium salt was completely dissolved, vinylene carbonate (VC), lithium fluorosulfonate (LiFS), the first additive, and the second additive were added to obtain a non-aqueous electrolyte.
[0057] In the non-aqueous electrolyte, the concentration of lithium hexafluorophosphate is 1M, the mass percentage of vinylene carbonate is 1.5%, the mass percentage of lithium fluorosulfonate is 0.1%, the mass percentage of the first additive is 1.4%, the mass percentage of the second additive is 1.1%, and the remainder is an organic solvent.
[0058] The structural formula of the first additive is as follows: The structural formula of the second additive is .
[0059] Steps 2-4 are performed in accordance with Example 1.
[0060] Example 10 1. Preparation of non-aqueous electrolytes: Ethylene carbonate (EC), diethyl carbonate (DEC), and methyl ethyl carbonate (EMC) were mixed in a mass ratio of EC:DEC:EMC = 3:2:5 to obtain an organic solvent. Lithium hexafluorophosphate (LiPF6) and lithium difluorooxalate borate (LiODFB) were then added. After the lithium salts were completely dissolved, vinylene carbonate (VC), lithium fluorosulfonate (LiFS), the first additive, and the second additive were added to obtain a non-aqueous electrolyte.
[0061] In the non-aqueous electrolyte, the concentration of lithium hexafluorophosphate is 0.9M, the concentration of lithium difluorooxalate borate is 0.1M, the mass percentage of vinylene carbonate is 1.5%, the mass percentage of lithium fluorosulfonate is 0.4%, the mass percentage of the first additive is 1.2%, the mass percentage of the second additive is 1.3%, and the remainder is an organic solvent.
[0062] The structural formula of the first additive is as follows: The structural formula of the second additive is .
[0063] Steps 2-4 are performed in accordance with Example 1.
[0064] Example 11 1. Preparation of non-aqueous electrolytes: Ethyl carbonate (EC), ethyl propionate (EP), and ethyl methyl carbonate (EMC) were mixed in a mass ratio of EC:EP:EMC = 3:2:5 to obtain an organic solvent. Lithium hexafluorophosphate (LiPF6) and lithium difluorooxalate borate (LiODFB) were then added. After the lithium salts were completely dissolved, vinylene carbonate (VC), lithium fluorosulfonate (LiFS), the first additive, and the second additive were added to obtain a non-aqueous electrolyte.
[0065] In the non-aqueous electrolyte, the concentration of lithium hexafluorophosphate is 0.8M, the concentration of lithium difluorooxalate borate is 0.2M, the mass percentage of vinylene carbonate is 1.5%, the mass percentage of lithium fluorosulfonate is 0.1%, the mass percentage of the first additive is 1.5%, the mass percentage of the second additive is 1.0%, and the remainder is an organic solvent.
[0066] The structural formula of the first additive is as follows: The structural formula of the second additive is .
[0067] Steps 2-4 are performed in accordance with Example 1.
[0068] Example 12 1. Preparation of non-aqueous electrolytes: Ethyl carbonate (EC), ethyl acetate (EA), and methyl ethyl carbonate (EMC) were mixed in a mass ratio of EC:EA:EMC = 3:2:5 to obtain an organic solvent. Lithium hexafluorophosphate (LiPF6), lithium bis(fluorosulfonyl)imide (LiFSI), and lithium difluorooxalate borate (LiODFB) were then added. After the lithium salts were completely dissolved, vinylene carbonate (VC), lithium fluorosulfonate (LiFS), the first additive, and the second additive were added to obtain a non-aqueous electrolyte.
[0069] In the non-aqueous electrolyte, the concentration of lithium hexafluorophosphate is 0.7M, the concentration of lithium difluorosulfonyl imide is 0.2M, the concentration of lithium difluorooxalate borate is 0.1M, the mass percentage of vinylene carbonate is 1.5%, the mass percentage of lithium fluorosulfonate is 0.2%, the mass percentage of the first additive is 1.8%, the mass percentage of the second additive is 0.7%, and the remainder is an organic solvent.
[0070] The structural formula of the first additive is as follows: The structural formula of the second additive is .
[0071] Steps 2-4 are performed in accordance with Example 1.
[0072] Example 13 1. Preparation of non-aqueous electrolytes: Ethylene carbonate (EC) and ethyl methyl carbonate (EMC) were mixed at a mass ratio of EC:EMC = 3:7 to obtain an organic solvent; lithium hexafluorophosphate (LiPF6) was then added, and after the lithium salt was completely dissolved, vinylene carbonate (VC), lithium fluorosulfonate (LiFS), the first additive, and the second additive were added to obtain a non-aqueous electrolyte.
[0073] In the non-aqueous electrolyte, the concentration of lithium hexafluorophosphate is 1M, the mass percentage of vinylene carbonate is 1.5%, the mass percentage of lithium fluorosulfonate is 0.3%, the mass percentage of the first additive is 0.9%, the mass percentage of the second additive is 0.1%, and the remainder is an organic solvent.
[0074] The structural formula of the first additive is as follows: The structural formula of the second additive is .
[0075] Steps 2-4 are performed in accordance with Example 1.
[0076] Example 14 1. Preparation of non-aqueous electrolytes: Ethylene carbonate (EC) and ethyl methyl carbonate (EMC) were mixed at a mass ratio of EC:EMC = 3:7 to obtain an organic solvent. Lithium hexafluorophosphate (LiPF6) was then added. After the lithium salt was completely dissolved, vinylene carbonate (VC), lithium fluorosulfonate (LiFS), the first additive, and the second additive were added to obtain a non-aqueous electrolyte.
[0077] In the non-aqueous electrolyte, the concentration of lithium hexafluorophosphate is 1M, the mass percentage of vinylene carbonate is 1.5%, the mass percentage of lithium fluorosulfonate is 0.3%, the mass percentage of the first additive is 3.0%, the mass percentage of the second additive is 1.0%, and the remainder is an organic solvent.
[0078] The structural formula of the first additive is as follows: The structural formula of the second additive is .
[0079] Steps 2-4 are performed in accordance with Example 1.
[0080] Comparative Example 1 1. Preparation of non-aqueous electrolytes: Ethylene carbonate (EC) and ethyl methyl carbonate (EMC) were mixed at a mass ratio of EC:EMC = 3:7 to obtain an organic solvent; lithium hexafluorophosphate (LiPF6) was then added, and after the lithium salt was completely dissolved, vinylene carbonate (VC), lithium fluorosulfonate (LiFS) and the first additive were added to obtain a non-aqueous electrolyte.
[0081] In the non-aqueous electrolyte, the concentration of lithium hexafluorophosphate is 1M, the mass percentage of vinylene carbonate is 1.5%, the mass percentage of lithium fluorosulfonate is 0.3%, the mass percentage of the first additive is 2.5%, and the remainder is an organic solvent.
[0082] The structural formula of the first additive is as follows: .
[0083] Steps 2-4 are performed in accordance with Example 1.
[0084] Comparative Example 2 1. Preparation of non-aqueous electrolytes: Ethylene carbonate (EC) and ethyl methyl carbonate (EMC) were mixed at a mass ratio of EC:EMC = 3:7 to obtain an organic solvent; lithium hexafluorophosphate (LiPF6) was then added, and after the lithium salt was completely dissolved, vinylene carbonate (VC), lithium fluorosulfonate (LiFS), and a second additive were added to obtain a non-aqueous electrolyte.
[0085] In the non-aqueous electrolyte, the concentration of lithium hexafluorophosphate is 1M, the mass percentage of vinylene carbonate is 1.5%, the mass percentage of lithium fluorosulfonate is 0.3%, the mass percentage of the second additive is 2.5%, and the remainder is an organic solvent.
[0086] The structural formula of the second additive is as follows: .
[0087] Steps 2-4 are performed in accordance with Example 1.
[0088] Comparative Example 3 1. Preparation of non-aqueous electrolytes: Ethylene carbonate (EC) and ethyl methyl carbonate (EMC) were mixed at a mass ratio of EC:EMC = 3:7 to obtain an organic solvent; lithium hexafluorophosphate (LiPF6) was then added, and after the lithium salt was completely dissolved, vinylene carbonate (VC), lithium fluorosulfonate (LiFS), and ethylene sulfate (DTD) were added to obtain a non-aqueous electrolyte.
[0089] In the non-aqueous electrolyte, the concentration of lithium hexafluorophosphate is 1M, the mass percentage of vinylene carbonate is 1.5%, the mass percentage of lithium fluorosulfonate is 0.3%, the mass percentage of vinyl sulfate is 2.5%, and the remainder is an organic solvent.
[0090] Steps 2-4 are performed in accordance with Example 1.
[0091] Comparative Example 4 1. Preparation of non-aqueous electrolytes: Ethylene carbonate (EC) and ethyl methyl carbonate (EMC) were mixed at a mass ratio of EC:EMC = 3:7 to obtain an organic solvent; lithium hexafluorophosphate (LiPF6) was then added, and after the lithium salt was completely dissolved, vinylene carbonate (VC), lithium fluorosulfonate (LiFS), and ethylene sulfate (DTD) were added to obtain a non-aqueous electrolyte.
[0092] In the non-aqueous electrolyte, the concentration of lithium hexafluorophosphate is 1M, the mass percentage of vinylene carbonate is 1.5%, the mass percentage of lithium fluorosulfonate is 0.3%, the mass percentage of vinyl sulfate is 2.5%, and the remainder is an organic solvent.
[0093] Steps 2-4 are performed in accordance with Example 1.
[0094] Comparative Example 5 1. Preparation of non-aqueous electrolytes: Ethylene carbonate (EC) and ethyl methyl carbonate (EMC) were mixed at a mass ratio of EC:EMC = 3:7 to obtain an organic solvent. Lithium hexafluorophosphate (LiPF6) was then added. After the lithium salt was completely dissolved, vinylene carbonate (VC), lithium fluorosulfonate (LiFS), and tris(trimethylsilyl)borate (TMSB) were added to obtain a non-aqueous electrolyte.
[0095] The non-aqueous electrolyte contains lithium hexafluorophosphate at a concentration of 1M, vinylene carbonate at a mass percentage of 1.5%, lithium fluorosulfonate at a mass percentage of 0.3%, tris(trimethylsilyl)borate at a mass percentage of 2.5%, and the remainder is an organic solvent.
[0096] Steps 2-4 are performed in accordance with Example 1.
[0097] Comparative Example 6 1. Preparation of non-aqueous electrolytes: Ethylene carbonate (EC) and ethyl methyl carbonate (EMC) were mixed at a mass ratio of EC:EMC = 3:7 to obtain an organic solvent. Lithium hexafluorophosphate (LiPF6) was then added. After the lithium salt was completely dissolved, vinylene carbonate (VC), lithium fluorosulfonate (LiFS), ethylene sulfate (DTD), and tris(trimethylsilyl)borate (TMSB) were added to obtain a non-aqueous electrolyte.
[0098] The non-aqueous electrolyte contains lithium hexafluorophosphate at a concentration of 1M, vinylene carbonate at a mass percentage of 1.5%, lithium fluorosulfonate at a mass percentage of 0.3%, vinyl sulfate at a mass percentage of 1.5%, tris(trimethylsilyl)borate at a mass percentage of 1.0%, and the remainder is an organic solvent.
[0099] Steps 2-4 are performed in accordance with Example 1.
[0100] Test case The batteries of the above embodiments and comparative examples were subjected to performance tests, and the specific test methods are as follows: (1) Initial DC Impedance (DCR) Test After capacity testing, the experimental battery was charged to 50% SOC. After resting for 30 minutes, the sampling voltage V0 at the start of discharge was recorded. Then, the battery was discharged at a 3C current I for 10 seconds, and the sampling voltage V1 at the end of discharge was recorded. The initial DC discharge impedance DCR of the experimental battery was calculated as (V0-V1) / I.
[0101] (2) Cyclic performance test Under test conditions of 25℃ and 45℃, the experimental batteries were subjected to charge-discharge cycle performance tests at a charge-discharge rate of 1C. The charge-discharge voltage range was set to 2.8-4.25V. The batteries were cycled for 600 cycles at room temperature and 400 cycles at high temperature. The DCR was measured every 100 cycles, and the capacity retention rate and DCR growth rate were recorded.
[0102] (3) High-temperature storage performance test At 25°C, the batteries of the examples and comparative examples were charged to 4.35V using a constant current and constant voltage of 0.2C, with a cutoff current of 0.05C. They were then discharged to 2.8V using a constant current of 0.2C, and their discharge capacity Q0 was recorded as the initial discharge capacity. Subsequently, the batteries were charged to 4.35V using a constant current and constant voltage of 0.2C, with a cutoff current of 0.05C. The fully charged experimental batteries were then placed in a 60°C oven for 28 days. After the high-temperature storage, the experimental cells were first discharged to 2.8V using a constant current of 0.2C, and their discharge capacity Q1 was recorded. Then, they were charged to 4.35V using a constant current and constant voltage of 0.2C, with a cutoff current of 0.05C. Finally, they were discharged to 2.8V using a constant current of 0.2C, and their discharge capacity Q2 was recorded. This process was repeated for three parallel experimental batteries, and the average value was taken. Therefore, the high-temperature storage capacity retention rate = Q1 / Q0*100%, and the high-temperature storage capacity recovery rate = Q2 / Q0*100%.
[0103] (4) High-temperature storage retention and recovery rate at 60℃ Under test conditions of 25℃ and 45℃, the experimental batteries were subjected to charge-discharge cycle performance tests at a charge-discharge rate of 1C. The charge-discharge voltage range was set to 2.8-4.25V. The batteries were cycled for 600 cycles at room temperature and 400 cycles at high temperature. The DCR was measured every 100 cycles, and the capacity retention rate and DCR growth rate were recorded.
[0104] The test results are shown in Table 1.
[0105] Table 1
[0106] As can be seen from Table 1, 1) The results of Examples 1-14 and Comparative Examples 1-6 show that, compared with traditional sulfur-containing and B-containing additives and their combinations, the electrolyte additive combination of the present invention can effectively reduce the initial room temperature DCR and low temperature DCR, and improve the normal and high temperature cycling and high-temperature performance.
[0107] 2) The test results of Comparative Examples 1-2 and Example 1 show that, compared with a single novel additive, the electrolyte additive combination of the present invention improves the DCR growth rate at normal and high temperatures and enhances the normal and high temperature cycling and high-temperature performance of the battery.
[0108] 3) The test results of Comparative Examples 1-2 and Comparative Examples 3-4 show that the first additive of the present invention, namely the sulfonate compound containing unsaturated alkanes, has better high-temperature cycling and high-temperature storage performance than conventional sulfuric acid ester compounds.
[0109] 4) The test results of Comparative Example 4 and Comparative Example 3 show that the LiFS additive can effectively improve the battery impedance and high-temperature performance.
[0110] 5) The test results of Comparative Examples 2 and 5 show that the second additive of the present invention can effectively reduce impedance compared with conventional borate ester compounds (TMSB).
[0111] In summary, it can be seen that the electrolyte of the present invention, which contains electrolyte additives with specific structures, can reduce the DCR growth rate at both ambient and high temperatures, effectively improve the high-temperature performance of the battery, and is very suitable for power batteries, energy storage batteries and other scenarios that require improved high-temperature storage and high-temperature cycling performance.
[0112] Although this specification describes embodiments, not every embodiment contains only one independent technical solution. This narrative style is merely for clarity. Those skilled in the art should consider the specification as a whole. The technical solutions in each embodiment can also be appropriately combined to form other embodiments that can be understood by those skilled in the art.
[0113] Therefore, the above description is only a preferred embodiment of this application and is not intended to limit the scope of this application; that is, all equivalent modifications made in accordance with the scope of the claims of this application shall be within the protection scope of the claims of this application.
Claims
1. A composite additive for non-aqueous electrolytes, characterized in that, It includes a first additive and a second additive; the first additive accounts for 0.9% to 3.0% of the total mass of the non-aqueous electrolyte; the second additive accounts for 0.1% to 1.5% of the total mass of the non-aqueous electrolyte; wherein, The general structural formula of the first additive is: ; In the formula, at least one of R1 and R2 is selected from F or fluorinated C. 6~12 Aryl, fluorinated C 6~12 heteroaryl or fluorinated C 1~3 Alkyl; and at least one of R1 and R2 is selected from substituted or unsubstituted C. 1~3 Unsaturated alkyl groups. The general structural formula of the second additive is ; In the formula, R1, R2, R3, and R4 are each independently selected from C1-C5 saturated hydrocarbon groups, unsaturated hydrocarbon groups, halohydrocarbon groups, cyclic hydrocarbon groups, cyano groups, and phenyl groups, and at least one of R1, R2, R3, and R4 is selected from substituted or unsubstituted C1-C5 groups. 1~3 Unsaturated alkyl groups.
2. The composite additive for non-aqueous electrolytes according to claim 1, characterized in that, The first additive is at least one of vinyl sulfonyl fluoride, 1,2,2-trifluorovinyl sulfonyl fluoride, 2-(trifluoromethyl)ethylene sulfonyl fluoride, and vinyltrifluoromethyl sulfone.
3. The composite additive for non-aqueous electrolytes according to claim 1, characterized in that, The second additive is at least one of trimethylvinylsilane, dimethyldivinylsilane, and trimethyl-2-fluorovinylsilane.
4. A non-aqueous electrolyte, characterized in that, It includes the composite additive as described in any one of claims 1-3, lithium salt, lithium fluorosulfonate, and organic solvent; wherein the lithium fluorosulfonate has a mass percentage content of 0.05% to 0.5% in the non-aqueous electrolyte.
5. The non-aqueous electrolyte according to claim 4, characterized in that, The lithium salt is selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium dioxarate borate, lithium difluorooxarate borate, lithium difluorooxarate phosphate, lithium bis(fluorosulfonyl)imide, and lithium bis(trifluoromethylsulfonyl)imide.
6. The non-aqueous electrolyte according to claim 4, characterized in that, The organic solvent is selected from at least one of cyclic carbonates, chain carbonates, cyclic carboxylic acid esters, chain carboxylic acid esters, cyclic ethers, chain ethers, tetrahydrofuran, 2-methyltetrahydrofuran, and 1,3-dioxolane.
7. The non-aqueous electrolyte according to claim 4, characterized in that, It also includes conventional additives, which are selected from one or more of vinylene carbonate, fluoroethylene carbonate, vinyl sulfate, 1,3-propane sulpholactone, 1,4-butane sulpholactone, methanedisulfonate, tris(trimethylsilane) phosphate, and tris(trimethylsilane) borate; the conventional additives are present in the non-aqueous electrolyte at a mass percentage of 0.1% to 5%.
8. A battery, characterized in that, It includes a positive electrode, a negative electrode, a separator located between the positive electrode and the negative electrode, and a non-aqueous electrolyte as described in any one of claims 4-7.
9. The lithium-ion battery according to claim 8, characterized in that, The positive electrode sheet includes a positive current collector and a positive active material layer disposed on the positive current collector. The positive active material layer contains a positive active material, which is a lithium phosphate with an olivine structure and / or a layered lithium nickel cobalt manganese oxide or a lithium nickel cobalt aluminum oxide.
10. The lithium-ion battery according to claim 8, characterized in that, The negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on the negative electrode current collector. The negative electrode active material layer contains a negative electrode active material, which is one or more of natural graphite, artificial graphite, silicon, and lithium titanate.